KEEFEKTIFAN PEMBELAJARAN E-LEARNING BERBASIS WEBSITE PADA MATA KULIAH TEORI BILANGAN DI IKIP PGRI SEMARANG - Muhammad Prayito (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2012)
The aim of this study is to know the effectiveness of learning based on Web at Number Theory lesson at IKIP PGRI Semarang. The implementation is focused at FPMIPA IKIP PGRI Semarang in fifth semester of mathematics education students which contain of 9 classes. Sampling technique in this study use convenience sampling procedure, where as the experimental is 5B and 5A as the control class and 5G as a class test. Independent variable of this research is the activity of student and learning result as dependent variable. The Data is obtained through observation and tests then we analyze by t test and regression test.. The results showed that implementation of learning achieve effective with characterized by: a) Mean of student learning result greater than KKM = 75, and in classical is more than 85% of students achieve point at 75. b) Effect of activity on the results of study is means that the active variable (X) gives a positive effect on learning result (Y). The value of the effect of creativity on learning result can be seen by R value in the table of Summary Model 0.867 = 86.7%. The Value indicates that the creativity of students affect learning result at 86.7%. c) The Mean of experimental class is 80.94 and 62.60 for the control class, so the class of experiments significantly better than the the control class. Based on the above explanation we conclude that learning based on web at Number Theory in Semarang PGRI IKIP is effective.